Low molecular weight heparin decreases mortality and major complication rates in moderately severe and severe acute pancreatitis–a systematic review and meta-analysis - Patoni, Cristina; Bunduc, Stefania; Frim, Levente; Veres, Dániel Sándor; Dembrovszky, Fanni; Éliás, Anna Júlia; Pálinkás, Dániel; Hegyi, Péter; Erőss, Bálint Mihály; Hegyi, Péter Jenő (Frontiers in Medicine, 2023)
Background Routine anticoagulation therapy in acute pancreatitis (AP) is not recommended by the guidelines in the field, although it is frequently used in clinical practice. Objectives We aimed to analyze the efficacy and safety of adding anticoagulants therapy to AP management. Methods The systematic search was performed in three databases on the 14th of October 2022 without restrictions. Randomized controlled trials (RCTs) and observational studies that reported the differences in the outcomes of AP for patients receiving anticoagulants (intervention group) in addition to the standard of care (SOC), compared to patients managed by SOC alone (control group), were eligible. A random-effects model was used to calculate the pooled odds ratios (OR) and mean differences (MD) with the corresponding 95%-confidence intervals (CI). We performed subgroup analysis for study design and disease severity, among other criteria. Results Of the 8,223 screened records, we included eight in the meta-analysis. Except one, all studies reported on low-molecular-weight heparin (LMWH). Both RCTs and observational studies reported results in favor of the LMWH group. Subgroup RCTs’ analysis revealed significantly decreased odds of mortality [OR 0.24; 95%CI 0.17–0.34] and multiple organ failure [OR 0.32; 95%CI 0.17–0.62] in the intervention group. Moreover, the need for endoscopic or surgical interventions [OR 0.41; 95%CI 0.28–0.61] were significantly reduced by LMWH. The subgroup analyzes for moderate and severe cases, respectively, yielded similar results. Due to limited data, we could no perform subgroup analysis for mild cases. Conclusion LMWH therapy reduces major complication rates in moderate and severe AP. Across all identified RCTs, LMWH were initiated early after AP diagnosis and improved its prognosis.